Analisis Karakteristik Marshall Campuran Aspal AC-WC Pada Kondisi Ambient Temperature - Fitra Aulia Azmi; Said Jalalul Akbar; Maizuar Maizuar (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Highways play a strategic role in supporting economic development, so the quality of pavement materials (flexible pavement) must meet previously established quality standards. The Asphalt Concrete Wearing Course (AC-WC) layer, as the topmost layer of flexible pavement, is susceptible to damage caused by aging triggered by environmental conditions, particularly ambient temperature. Temperatures above 30°C are known to accelerate plastic deformation (rutting) and reduce pavement bearing capacity. The Meteorology, Climatology, and Geophysics Agency indicates that temperatures in Lhokseumawe City, North Aceh, range from 33.7–35.3°C with day-night fluctuations that could potentially accelerate the degradation of mechanical properties. This study aims to analyze the Marshall characteristics of AC-WC asphalt mixtures under ambient temperature conditions. The testing was conducted with varying exposure times of 0, 15, 30, 45, 60, 75, and 90 days at a minimum temperature of 23.90°C and a maximum temperature of 31.80°C, with an average humidity of 87.93%. The test results showed that the AC-WC asphalt mixture experienced a decrease in stability value of 21.37% and an increase in flow value of 36.36%, resulting in a decrease in the Marshall Quotient (MQ) value of 42.52%.